Failure evaluation and corrosion rate prediction method for copper alloy material at different seawater flow velocities

Through a combination of simulation calculation and experiment, the corrosion behavior of copper alloys under different seawater flow rates is studied, and its microstructure and kinetic parameters are analyzed, which solves the corrosion resistance of copper alloys under high flow rates and high pressure conditions in the prior art. The problem is to achieve quantitative prediction and protective design of its corrosion tendency.

CN119510272AActive Publication Date: 2025-02-25BEIJING UNIV OF CHEM TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411520675.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-25
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The prior art lacks systematic research on the corrosion behavior of copper alloys in seawater environments and their microstructure evolution, especially under high flow velocity and high pressure conditions, resulting in a decrease in corrosion resistance.

Method used

Through combining experiments and simulation calculations, density functional theory (DFT) was used to establish the corrosion structure model of copper alloy at different seawater flow rates, and the corrosion kinetic parameters such as dissolution activation energy barrier, dissolution potential and dissolution rate were analyzed, and the weight loss was achieved through macroscopic corrosion Experimental exploration of the influence of different seawater flow rates on alloy corrosion behavior.

Benefits of technology

Quantitative characterization and prediction of the corrosion tendency of copper alloys in seawater dynamic environments is realized, scientifically based on its protection design, and corrosion rate prediction model based on atomic axial stretching is established.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107971100000041
    Figure BDA0005107971100000041
  • Figure BDA0005107971100000042
    Figure BDA0005107971100000042
  • Figure BDA0005107971100000055
    Figure BDA0005107971100000055
Patent Text Reader

Abstract

The invention discloses a copper alloy material failure evaluation and corrosion rate prediction method under different seawater flow rates, and belongs to the field of marine environment copper alloy corrosion. The method comprises the following steps: firstly, analyzing an XRD (X-Ray Diffraction) spectrum of the copper alloy corroded by flowing seawater, and determining a micro-strain level and dislocation density; atomic-scale axial tensile strain is applied to the crystal face (111) according to the density functional theory, and microstructure models under different seawater flow velocities are established. And analyzing the dissolution potential, surface energy, work function and dissolution activation energy barrier of copper atoms on the alloy surface, and exploring the relationship between the dissolution rate and the activation energy barrier. And establishing a prediction model of the seawater flow velocity and the copper alloy corrosion rate in the seawater dynamic environment. According to the method, the corrosion dynamic characteristics of the copper alloy at different seawater flow velocities are obtained, and the analysis of the atomic-scale axial tension induced copper alloy corrosion failure dynamic process is realized, so that a theoretical basis is provided for the anti-corrosion design of a copper alloy component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the research field of copper alloy corrosion and protection in marine environment, and in particular, involves simulating the influence of different seawater flow rates on the microstructure of copper alloy, and analyzing corrosion kinetic parameters such as dissolution activation energy barrier, dissolution potential and dissolution rate to achieve quantitative characterization and prediction of alloy corrosion tendency in dynamic and complex seawater environment. This invention is of great significance to improving the safety, reliability and economic benefits of seawater engineering. Background Art

[0002] Propellers and seawater pipelines are key components of ships. Their durability in the dynamic environment of seawater is directly related to the safety and operating efficiency of ships. Copper alloys are widely used in seawater engineering due to their excellent mechanical properties and corrosion resistance. However, under extremely high flow rates and high pressure conditions, copper alloys face serious corrosion challenges. Their corrosion mechanism in seawater environments has not yet been fully clarified, which limits the long-term reliability of their applications. Therefore, in-depth research on the corrosion behavior of copper alloys in the dynamic environment of seawater not only provides a scientific basis for their protection, but also has important engineering application value.

[0003] In recent years, studies have shown that mechanical factors such as seawater flow rate and pressure significantly affect the corrosion process of copper alloys. Under high flow conditions, the surface microstructure of the copper alloy will be damaged, indicating that the increase in seawater flow rate promotes the mass transfer process and generates wall shear stress, accelerating the corrosion rate. When the seawater flow rate exceeds the critical flow rate, corrosion products will fall off the alloy surface, further accelerating the corrosion process. In addition, the effect of different seawater flow rates will also induce local lattice distortion on the surface of the copper alloy, reduce the metal equilibrium potential, and make the alloy more susceptible to corrosion.

[0004] Current technology lacks a method that combines experiments with simulation calculations to systematically study the corrosion behavior of copper alloys in seawater environments and the evolution of their microstructures. The present invention proposes an innovative research method, which constructs a corrosion structure model of copper alloys at different seawater flow rates based on density functional theory (DFT), and analyzes its corrosion kinetic parameters such as dissolution activation energy barrier, dissolution potential and dissolution rate. At the same time, through macroscopic corrosion weight loss experiments, the influence of different seawater flow rates on the corrosion behavior of alloys is explored. The study found that with the increase of seawater flow rate, the mass loss and corrosion rate of copper alloys increased significantly, and the corrosion resistance decreased. This method combines simulation and experimental results to provide a scientific basis for the corrosion protection of copper alloys in the dynamic environment of seawater, and at the same time establishes a copper alloy corrosion rate prediction model based on atomic-level axial stretching. Summary of the invention

[0005] In order to solve the limitations of the prior art, the present invention aims to combine experiments with simulation calculations to study the corrosion behavior of copper alloys in a dynamic seawater environment and develop a method for predicting the corrosion failure behavior of copper alloys based on atomic-level axial tensile strain. The method first determines the microstrain level and dislocation density under different seawater flow rates by analyzing the XRD spectrum of the copper alloy after flowing seawater corrosion. Then, the density functional theory is used to apply atomic-level axial tensile strain to the (111) crystal plane to establish a microstructure model under different seawater flow rates. Further combined with the structural evolution under microstrain conditions, the dissolution potential, surface energy, work function and dissolution activation energy barrier of copper atoms on the alloy surface are analyzed to explore the relationship between the dissolution rate and the activation energy barrier. The intrinsic diffusion coefficient of copper atoms is calculated by the modified Sutherland equation, and a prediction model for the seawater flow rate and the corrosion rate of copper alloys in a dynamic seawater environment is established. The present invention quantitatively simulates the influence of seawater flow rate on the corrosion behavior of copper alloys, analyzes the corrosion kinetic characteristics of copper alloys under different seawater flow rates, and realizes the analysis of the corrosion failure kinetic process of copper alloys induced by atomic-level axial tension, thereby providing a theoretical basis for the anti-corrosion design of copper alloy components.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical scheme: the microstrain value, axial tensile strain value and dislocation density of the copper alloy under different seawater flow rates are determined by XRD analysis of the diffraction peak shape and peak width. The density functional theory (DFT) is used to establish a microstructure model of the copper alloy, and the strain is applied by precisely controlling the lattice axial parameters to establish a (111) crystal plane z direction. The vacuum layer is used to release the top two layers of atoms to simulate the alloy surface, while the other layers of atoms are fixed to simulate the internal structure of the alloy. The DMol3 module of Materials studio is used for geometry optimization, and the COSMO-type conductor shielding model and the dielectric constant of seawater are used to simulate the seawater environment. In addition, the DFT semi-nuclear pseudopotential DSPP method is used to deal with the relativistic effect of nuclear electrons, and the dual numerical plus polarization DNP basis set is used to calculate the corrosion kinetic characteristic parameters of copper alloys. Through the transition state theory (TST) equivalent dissolution activation barrier, the linear and quadratic simultaneous transfer (LST / QST) are used to optimize the dissolution transition state of copper alloys, and the linear relationship between the dissolution rate and the activation energy barrier is established. The intrinsic diffusion coefficient of copper atoms obtained by the Sutherland equation is used to establish a model for predicting the corrosion rate of copper alloys in a dynamic seawater environment.

[0007] The method for evaluating the failure of copper alloy materials and predicting their corrosion rates under different seawater flow rates is characterized in that the method comprises the following steps:

[0008] (1) Analysis of atomic-level axial tensile strain of copper alloy: Based on the X-ray diffraction (XRD) test results of copper alloy after corrosion at different seawater flow rates, the microstrain value is determined by analyzing the diffraction peak shape and using peak broadening to obtain the axial tensile microstrain and dislocation density of the alloy's internal lattice;

[0009] By determining the half-width β and Bragg angle θ of the diffraction peak, the axial tensile microstrain ε of the copper alloy structure under different seawater flow rates is calculated according to formula (1):

[0010]

[0011] The Scherrer formula is used to calculate the diffraction peak broadening caused by grain size, K is the shape factor (usually 0.9), λ is the X-ray wavelength, and the grain size d and dislocation density ρ of the copper alloy under different seawater flow rates are determined according to formula (2) and formula (3):

[0012]

[0013] This method shows that as the seawater flow rate increases, the axial tensile strain and dislocation density of the copper alloy increase, indicating that high seawater flow rates can cause changes in the surface structural defects of the alloy, accelerate the corrosion process of the copper alloy, and lead to a decrease in its corrosion resistance.

[0014] (2) Quantitatively simulate the mechanical effect of different seawater flow rates on the alloy surface. Based on the axial tensile microstrain ε determined in step (1), a microstructure model of the copper alloy with different seawater flow rates is established by atomic-level axial tensile strain: by regulating the lattice axial parameters, strain is applied along the (111) crystal plane direction. By precisely controlling the lattice constant of the copper alloy in the seawater environment, the lattice parameters in the (111) direction are gradually increased, and the axial tensile strain corresponding to the increase in flow rate is introduced. The lattice parameters in other directions are kept unchanged, thereby achieving atomic-level strain control applied to the (111) crystal plane.

[0015] (3) Calculation of the dissolution potential of the copper alloy or the shift of the dissolution potential of the copper alloy under different seawater flow rates in a dynamic seawater environment: Based on the axial tensile microstrain determined in step (1) and the microstructure model under different seawater flow rates established in step (2), the energy of the alloy vacancy model under the action of different flowing seawater is calculated, and then the dissolution potential of the copper alloy or the shift of the dissolution potential of the copper alloy under different seawater flow rates is obtained;

[0016] The energy E of the alloy model without axial tensile strain is determined by alloy and the energy of the alloy model under axial tensile strain and the energy E of the alloy vacancy model without axial tensile strain alloy-vac and the energy of the alloy vacancy model under axial tensile strain According to formula (4), the shift of the metal dissolution electrode potential caused by the introduction of tensile strain in copper alloy is calculated:

[0017]

[0018] This method quantitatively analyzes the dissolution tendency of copper alloy in a flowing seawater environment by describing the dissolution electrode potential of the metal during the corrosion process. The results show that as the seawater flow rate increases, the dissolution electrode potential of the copper alloy shifts to a negative direction, resulting in a decrease in the metal dissolution potential and a decrease in corrosion resistance, thereby verifying that the model in step (2) is suitable for simulating the corrosion behavior of copper alloys in a dynamic seawater environment.

[0019] (4) Calculation of the surface energy and work function of the copper alloy under different seawater flow rates in a dynamic seawater environment: Based on steps (1)-(3), by constructing a (111) crystal plane alloy structure model under different axial tensile strains, energy minimization calculations are performed to obtain the energy state of the alloy surface. By calculating the electric potential of the alloy model under different seawater flow rates and the contact potential difference between the alloy model and the seawater interface, the effect of seawater flow rate on the surface structure and stability of the copper alloy, i.e., the corresponding work function, is quantitatively analyzed.

[0020] By determining the total energy E of the surface model with different axial tensions in step (2) slab and alloy bulk atomic N atoms The average energy E bulk According to formula (5), the surface energy state E of the alloy under different seawater flow rates is calculated. surf :

[0021]

[0022] The contact potential difference between copper alloy and seawater solution and the potential value ψ of the alloy model at different seawater flow rates, and the work function Φ required for the copper alloy to remove surface electrons at different seawater flow rates is calculated according to formula (6):

[0023]

[0024] The simulation results of this method show that as the seawater flow rate increases, the surface energy of the copper alloy increases, the work function decreases, the energy state of the atoms on the alloy surface rises, and electrons are more likely to escape from the surface, further indicating that the flowing seawater accelerates the corrosion kinetics of the alloy.

[0025] (5) Calculation of activation energy barriers and dissolution rates of copper alloys under different seawater flow rates in a dynamic seawater environment: Based on steps (1)-(4), the activation energy barriers of copper alloy atoms under different flow rates are quantitatively analyzed using the transition state search method, and then the dissolution rate is calculated;

[0026] The activation energy barrier ΔE(t) of alloy dissolution under different seawater flow rates was obtained by transition state search, where σ is the degeneracy of the reaction path and takes the value of 1, P 0 is the standard gas pressure of 0.1 MPa, t is the corresponding room temperature or atmospheric temperature, and h is Planck's constant of 6.626×10 -34 J.s,k b The Boltzmann constant is 1.381×10 -23 J.K. -1 , R is the universal gas constant 8.314 J·K -1 ·mol -1 , Δn=0 in the single molecule reaction, and the dissolution rate k under different seawater flow rates is calculated according to formula (7): TST :

[0027]

[0028] This method shows that as the seawater flow rate increases, the dissolution activation energy barrier decreases significantly, the dissolution resistance of metal atoms decreases, and the dissolution rate increases accordingly. This method can accurately evaluate the influence of atomic-level axial tensile strain on the alloy corrosion kinetics under different seawater flow rates, and realize the simulation and prediction of copper alloy corrosion tendency in high flow rate environment.

[0029] (6) Establishment of a prediction model for copper alloy corrosion rate based on atomic-level axial tension under dynamic seawater environment: Based on the axial tensile strain model of copper alloy under different seawater flow rates in step (1)-step (2), the dissolution activation energy barrier is determined by transition state search. According to formula (7), a linear relationship between the dissolution rate and the activation energy barrier is established to obtain the dissolution rate of copper alloy under different seawater flow rates. Combined with the intrinsic diffusion coefficient D of copper atoms, the correction coefficient k, the time conversion factor T and other parameters, the above-mentioned pairs of different seawater flow rate variables and the dissolution rate x are fitted, and the dissolution rate spectrum is converted into a relationship model between the seawater flow rate and the copper alloy corrosion rate y under the dynamic seawater environment. The unit is mm / a (millimeter / year), where k is the correction coefficient, D is the intrinsic diffusion coefficient, T is the time conversion factor, α is the fitting coefficient, and C is a parameter related to the alloy. It can be obtained by fitting x and the dissolution rate to achieve accurate prediction of the corrosion rate of copper alloys in complex seawater environments.

[0030] In a preferred embodiment of the present invention, the copper alloy types include manganese aluminum bronze alloy (MAB) for propellers and copper nickel alloy (B10) for seawater pipelines.

[0031] In a preferred embodiment of the present invention, in step (1), the seawater flow rate of the manganese aluminum bronze alloy MAB used for the propeller is 0-12 m / s, including 0, 2, 4, 6, 8, and 12 m / s.

[0032] In a preferred embodiment of the present invention, in step (1), the seawater flow rate of the copper-nickel alloy B10 used for the seawater pipeline is 0-4 m / s, including 0, 1, 2, 3, and 4 m / s.

[0033] In a preferred embodiment of the present invention, in step (2), a copper alloy microstructure model is established based on atomic-level axial tensile strain, and the method for simulating seawater flow rate is as follows: the axial tensile strain values ​​of the copper alloy at different seawater flow rates are obtained by XRD analysis, and the microstructure model of the copper alloy is established by using density functional theory (DFT), and the lattice axial parameters are precisely controlled to apply strain, and the microstructure model of the copper alloy is established in the z direction of the (111) crystal plane. The vacuum layer releases the top two layers of atoms to simulate the alloy surface, while fixing the other layers of atoms to simulate the internal structure of the alloy, keeping the lattice parameters in other directions unchanged, gradually increasing the axial lattice parameters, introducing axial tensile strain corresponding to the increase in flow rate, and realizing atomic-level strain control of the copper alloy.

[0034] In a preferred embodiment of the present invention, in steps (3)-(5), the simulation calculation method of the characteristic parameters of the corrosion kinetics of the copper alloy under different seawater flow rates is as follows: the PBE generalized gradient approximation (GGA) method in the Materials Studio simulation package is used for geometric structure optimization, the Brillouin zone of the alloy surface is sampled on a (2×2×1) k-point grid by the Monkhorst-Pack method, the COSMO-type conductor shielding model is used, and the seawater environment is simulated in combination with the seawater dielectric constant, an implicit seawater solvation model is established, the DFT semi-core pseudopotential DSPP method is used to process the relativistic effect of nuclear electrons, the basis set adopts dual numerical plus polarization DNP, and the convergence tolerance and self-consistent field (SCF) convergence standard are set to 2.72×10 -3 eV to calculate the corrosion kinetic characteristic parameters of copper alloy in the dynamic environment of seawater.

[0035] In a preferred embodiment of the present invention, in step (6), the calculation method of the dissolution rate and corrosion rate of the copper alloy under different seawater flow rates is as follows: using the transition state theory (TST) equivalent dissolution activation energy barrier, optimizing the dissolution transition state of the copper alloy in the seawater environment by the linear simultaneous transfer (LST) and quadratic simultaneous transfer (QST) methods, calculating the dissolution rate based on the Sobereva method, establishing a linear relationship between the dissolution rate and the activation energy barrier, and using the intrinsic diffusion coefficient of copper atoms obtained by the Sutherland equation to convert the relationship between the seawater flow rate and the dissolution rate into a prediction model for the corrosion rate in the dynamic seawater environment.

[0036] In a preferred embodiment of the present invention, the corrosion rate prediction model of MAB alloy in a dynamic seawater environment is: R 2=0.998(correction coefficient k1=1.91×10 -7 , the intrinsic diffusion coefficient of copper atoms D = 1.06 × 10 -7 , time conversion factor T = 3.15 × 10 7 , α=-20.34).

[0037] In a preferred embodiment of the present invention, the corrosion rate prediction model of B10 alloy in a dynamic seawater environment is: R 2 =0.996(correction coefficient k2=2.78×10 -9 , the intrinsic diffusion coefficient of copper atoms D = 1.06 × 10 -7 , time conversion factor T = 3.15 × 10 7 , β=-0.29).

[0038] In the preferred embodiment of the present invention, the corrosion behavior of copper alloy in the dynamic environment of seawater is predicted, and the simulated predicted corrosion rate is consistent with the measured value trend, and the prediction accuracy deviation is less than 10%. The dissolution acceleration mechanism of copper alloy in seawater environment is revealed, providing a theoretical basis for its anti-corrosion design.

[0039] Compared with the existing copper alloy corrosion rate prediction method, the present invention has the following advantages:

[0040] The present invention can not only predict the corrosion rate of alloys through simulation calculations, but also deeply analyze and understand the microscopic mechanisms in the corrosion process, such as electronic behavior, chemical reaction paths, etc. This in-depth understanding promotes the innovation of new alloy design and provides a scientific basis for the development of corrosion-resistant materials and improved structural design.

[0041] The present invention obtains corrosion data of alloys under specific conditions through experiments, and uses simulation calculations for in-depth analysis, making the prediction of corrosion rate more accurate and reliable. This process greatly improves the accuracy of prediction results by simulating corrosion reactions under different environmental parameters and supplementing experimental verification.

[0042] The method of the present invention effectively reduces the number and scale of experiments by optimizing the experimental design and combining simulation calculation to predict the corrosion process. The method combining experiments and simulation calculations significantly improves the efficiency and accuracy of predicting the corrosion rate of alloys in a flowing seawater environment, which has important practical value and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The present invention will be further described below in conjunction with the accompanying drawings. The accompanying drawings are only used to schematically illustrate and explain the present invention and do not limit the scope of the present invention.

[0044] Figure 1 1 is the XRD spectrum of the MAB alloy at different seawater flow rates in Example 1.

[0045] Figure 2 It is the microstrain level and dislocation density of the MAB alloy at different seawater flow rates in Example 1.

[0046] Figure 3 The copper alloy microstructure model and the change in dissolution electrode potential caused by strain in Example 1 at different seawater flow rates.

[0047] Figure 4 are the surface energy and work function of the MAB alloy under atomic axial tensile strain in Example 1.

[0048] Figure 5 Activation energy barrier and dissolution rate of MAB alloy at different seawater flow rates in Example 1.

[0049] Figure 6 It is the corrosion weight loss rate and corrosion rate prediction model of the MAB alloy under different seawater flow rates in Example 1.

[0050] Figure 7 It is the XRD spectrum of B10 alloy at different seawater flow rates in Example 2.

[0051] Figure 8 It is the microstrain level and dislocation density of B10 alloy at different seawater flow rates in Example 2.

[0052] Fig. 9 are the surface energy and work function of the B10 alloy under atomic axial tensile strain in Example 2.

[0053] Fig.10 These are the activation energy barriers and dissolution rates of B10 alloy at different seawater flow rates in Example 2.

[0054] Fig.11 It is the corrosion weight loss rate and corrosion rate prediction model of B10 alloy under different seawater flow rates in Example 2. DETAILED DESCRIPTION

[0055] The present invention is described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited by the specific embodiments.

[0056] Example 1: High manganese aluminum bronze alloy (MAB) for propeller

[0057] GSAS-Ⅱ software was used to analyze the XRD diffraction peaks of MAB alloy under different seawater flow rates. Figure 1 As shown. The microstrain is determined by peak broadening, and the axial tensile strain and dislocation density of the alloy's internal lattice are obtained. As the seawater flow rate increases from 0 to 12 m / s, the axial tensile strain and dislocation density of the copper alloy gradually increase. Figure 2As shown in the figure, the atomic-level axial tensile strain of the MAB alloy at different seawater flow rates is 0.98%, 1.02%, 1.45%, 2.05%, 2.55%, and 3.32%, respectively. This indicates that high seawater flow rates cause an increase in structural defects on the alloy surface, resulting in reduced corrosion resistance.

[0058] The DMol3 module of Materials Studio was used to establish a 3×3×4 MAB alloy microstructure model with a lattice constant of The element composition of the alloy is CuAlMn, in which the content ratio of copper, aluminum and manganese is 22:12:2. Figure 3 As shown, the PBE DFT method is used to optimize the geometric structure, and the z-axis direction of the model is set Vacuum layer to prevent interaction with adjacent plates. The two layers of atoms in the surface and subsurface layers relax, and the two layers of atoms in the bottom are fixed as a matrix. The tensile strain caused by the flow of seawater reduces the dissolution electrode potential of the alloy, thereby accelerating the corrosion process. The strain causes the atomic bonds on the alloy surface to stretch, the interaction between atoms is weakened, and the corrosion kinetics process is accelerated.

[0059] The DFT calculation results show that the surface energy of MAB alloy increases with the strain under different elastic strains, the surface atomic distance increases, and it is in a high energy state. Microstrain causes the redistribution of surface electron density, which changes the work function and chemical potential of the alloy. Figure 4 As shown, with the increase of strain, the work function decreases from 4.84eV to 4.62eV. The decrease in work function indicates a negative shift in corrosion potential, an increase in surface activity, and an acceleration of the dissolution process of the copper alloy.

[0060] Simulate the activation energy barrier of copper alloy dissolution at different seawater flow rates, such as Figure 5 As shown in the figure: (1) the initial state of the MAB alloy (IS); (2) the surface Cu atoms dissolve out and leave metal vacancies on the surface (VAC1); (3) the transition state of Cu atom migration (TS); (4) the subsurface Cu atoms spontaneously migrate to the surface vacancies to form subsurface vacancies (VAC2); (5) the Cu atoms further dissolve to form a divacancy structure (FS). The increase in seawater flow rate reduces the dissolution resistance of the alloy and significantly accelerates the dissolution kinetics. Based on the transition state theory (TST) of the partition function, the linear correlation between the dissolution rate and the seawater flow rate is obtained by fitting the dissolution rate and the activation energy barrier at different flow rates.

[0061] On the basis of establishing a linear relationship between the dissolution rate and the seawater flow rate, the intrinsic diffusion coefficient D of copper atoms, the correction coefficient k, the time conversion factor T and other parameters were combined to fit the above-mentioned pairs of different seawater flow rate variables and the dissolution rate, and the dissolution rate map was converted into a prediction model for the seawater flow rate and the corrosion rate of the copper alloy in the dynamic seawater environment. Through experimental verification, a corrosion weight loss experiment was carried out in artificial seawater, and the corrosion weight loss rate of the MAB alloy immersed in different seawater flow rates for 12 hours was determined. The results show that the corrosion rate of the MAB alloy axial tensile strain model in the dynamic seawater environment is basically consistent with the experimental corrosion rate, and the prediction accuracy deviation is less than 10%, which can achieve accurate prediction of the corrosion rate of copper alloys in complex seawater environments. Figure 6 As shown, the corrosion rate prediction model of MAB alloy in seawater dynamic environment was finally obtained by fitting: R 2 =0.998(correction coefficient k1=1.91×10 -7 , the intrinsic diffusion coefficient of copper atoms D = 1.06 × 10 -7 , time conversion factor T = 3.15 × 10 7 , α=-20.34).

[0062] Example 2: B10 alloy for seawater pipelines

[0063] GSAS-Ⅱ software was used to analyze the XRD diffraction peaks of B10 alloy under different seawater flow rates. Figure 7 As shown. The microstrain is determined by peak broadening, and the axial tensile strain and dislocation density of the alloy's internal lattice are obtained. As the seawater flow rate increases from 0 to 4 m / s, the axial tensile strain and dislocation density of the copper-nickel alloy gradually increase. Figure 8 As shown in the figure, the atomic-level axial tensile strain of B10 alloy at different seawater flow rates is 0.23%, 0.25%, 0.30%, 0.36% and 0.72%, respectively. This indicates that high seawater flow rate causes more surface structural defects of B10 alloy and accelerates corrosion tendency.

[0064] The DMol3 module of Materials Studio was used to establish a 3×3×4 B10 alloy microstructure model with a lattice constant of The element composition of the alloy is CuNi, in which the ratio of copper to nickel is 24:12. The geometry is optimized using the PBE DFT method, and the z-axis direction of the model is set The vacuum layer is used to prevent interaction with adjacent plates. The two layers of atoms in the surface and subsurface layers are relaxed, and the two layers of atoms in the bottom are fixed as the matrix. The DFT calculation results show that the surface energy of B10 alloy increases with the increase of strain under different elastic strains, the surface atomic spacing increases, and it is in a high energy state. Fig. 9As shown in Figure 5, with the increase of axial tensile strain, the work function decreases from 4.63 eV to 4.55 eV. The decrease in work function reflects the negative shift of corrosion potential, which accelerates the dissolution process of B10 alloy.

[0065] The activation energy barrier of B10 alloy dissolution under simulated seawater flow rates is as follows: Fig.10 As shown in the figure, the increase of seawater flow rate from 0-4m / s reduces the dissolution resistance of the alloy and accelerates the dissolution kinetics of the alloy. Based on the transition state theory (TST) of the partition function, the linear relationship between the dissolution rate and the seawater flow rate is obtained by fitting the dissolution rate and the activation energy barrier at different flow rates.

[0066] On the basis of establishing a linear relationship between the dissolution rate and the seawater flow rate, the intrinsic diffusion coefficient D of copper atoms, the correction coefficient k, the time conversion factor T and other parameters were combined to fit the above-mentioned pairs of different seawater flow rate variables and the dissolution rate, and the dissolution rate spectrum of the B10 alloy was converted into a corrosion rate prediction model under the dynamic seawater environment. Through experimental verification, a corrosion weight loss experiment was carried out in artificial seawater, and the corrosion weight loss rate of the B10 alloy immersed in different seawater flow rates for 12 hours was determined. The results show that the corrosion rate of the axial tensile strain model of the B10 alloy in the dynamic seawater environment is basically consistent with the experimental corrosion rate. It further illustrates that the model can accurately evaluate the influence of seawater flow on the material corrosion kinetics process, realize the simulation and prediction of the corrosion tendency of high-flow rate copper alloys, and overcome the difficulty of experimental measurement under high-flow rate conditions. Figure 6 As shown in the figure, the corrosion rate prediction model of B10 alloy in seawater dynamic environment is finally obtained by fitting: R 2 =0.996(correction coefficient k2=2.78×10 -9 , the intrinsic diffusion coefficient of copper atoms D = 1.06 × 10 -7 , time conversion factor T = 3.15 × 10 7 , β=-0.29).

[0067] Figure 1 1 is the XRD pattern of the MAB alloy at different seawater flow rates in Example 1. As the seawater flow rate increases from 0 to 12 m / s, the axial tensile strain and dislocation density of the (111) crystal plane of the MAB alloy increase.

[0068] Figure 2 The microstrain level and dislocation density of the MAB alloy at different seawater flow rates in Example 1. The atomic-level axial tensile strain of the MAB alloy at different seawater flow rates is 0.98%, 1.02%, 1.45%, 2.05%, 2.55%, and 3.32%, respectively. This indicates that high seawater flow rates can cause changes in the surface structural defects of the alloy, accelerate the corrosion process of the copper alloy, and reduce its corrosion resistance.

[0069] Figure 3 The microstructure model of the copper alloy under different seawater flow rates and the change in dissolution electrode potential caused by strain in Example 1. The tensile strain generated by the flow of seawater on the alloy surface reduces the dissolution electrode potential of the alloy and accelerates the corrosion kinetics process. This shows that the microstrain caused by the seawater flow rate causes the atomic bonds on the alloy surface to stretch, and the interaction between atoms is weakened, proving the decrease in the stability of the copper alloy.

[0070] Figure 4 is the surface energy and work function of the MAB alloy under atomic axial tensile strain in Example 1. The results show that the surface energy of the alloy increases with increasing strain, the surface atomic spacing increases, and it is in a high energy state. Microstrain causes the surface electron density to be redistributed, changing the work function and chemical potential. As the strain increases, the work function decreases, the corrosion potential shifts negatively, and the dissolution process of the copper alloy is accelerated.

[0071] Figure 5 The activation energy barrier and dissolution rate of MAB alloy dissolution at different seawater flow rates in Example 1 show that the increase in flow rate reduces the dissolution resistance of the alloy and significantly accelerates the dissolution kinetics. Based on the transition state theory (TST) of the partition function, the linear model of dissolution rate and seawater flow rate is obtained by fitting the relationship between dissolution rate and activation energy barrier at different flow rates.

[0072] Figure 6 This is the corrosion weight loss rate and corrosion rate prediction model of the MAB alloy under different seawater flow rates in Example 1. The results show that with the increase of seawater flow rate, the corrosion rate of the MAB alloy increases significantly, indicating that the seawater flow rate accelerates the corrosion process. Compared with the measured corrosion rate, it shows that the model can effectively predict the corrosion behavior of the MAB alloy in the dynamic environment of seawater.

[0073] Figure 7 : is the XRD spectrum of the B10 alloy at different seawater flow rates in Example 2. As the seawater flow rate increases from 0-4 m / s, the axial tensile strain and dislocation density of the B10 alloy on the (111) crystal plane increase.

[0074] Figure 8 It is the microstrain level and dislocation density of B10 alloy at different seawater flow rates in Example 2. The atomic-level axial tensile strain of MAB alloy at different seawater flow rates is 0.23%, 0.25%, 0.30%, 0.36%, and 0.72%, respectively, which indicates that high seawater flow rates can cause changes in the surface structural defects of the alloy.

[0075] Fig. 9It is the surface energy and work function of the B10 alloy under atomic axial tensile strain in Example 2. The results show that the surface energy of the alloy increases with the increase of strain, the surface atomic spacing increases, and it is in a high energy state. Microstrain causes the redistribution of surface electron density, the increase of axial tensile strain leads to a decrease in work function, a negative shift in corrosion potential, and accelerates the dissolution process of the B10 alloy.

[0076] Fig.10 The activation energy barrier and dissolution rate of B10 alloy at different seawater flow rates in Example 2 show that the increase in flow rate reduces the dissolution resistance of the alloy and significantly accelerates the dissolution kinetics. Based on the transition state theory (TST) of the partition function, the linear model of dissolution rate and seawater flow rate is obtained by fitting the relationship between the dissolution rate and activation energy barrier of B10 alloy at different flow rates.

[0077] Fig.11 This is the corrosion weight loss rate and corrosion rate prediction model of B10 alloy under different seawater flow rates in Example 2. The results show that with the increase of seawater flow rate, the corrosion rate of B10 alloy increases significantly, indicating that the seawater flow rate accelerates the corrosion process. Compared with the measured corrosion rate, it shows that the model can effectively predict the corrosion behavior of B10 alloy in the dynamic environment of seawater.

[0078] The above specific embodiments describe the basic principles and main features of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments, and any changes or modifications that are not thought of through creative work should be included in the protection scope of the present invention. Without departing from the scope of the present invention, the present invention will also have various changes and improvements, and these changes and improvements will fall within the scope of protection required.

Claims

1. A method for evaluating the failure of copper alloy materials under different seawater flow rates, characterized in that: The following steps are involved: (1) Analysis of atomic-level axial tensile strain of copper alloy: Based on the X-ray diffraction (XRD) test results of copper alloy after corrosion at different seawater flow rates, the microstrain value is determined by analyzing the diffraction peak shape and using peak broadening to obtain the axial tensile microstrain and dislocation density of the alloy's internal lattice; By determining the half-width β and Bragg angle θ of the diffraction peak, the axial tensile microstrain ε of the copper alloy structure under different seawater flow rates is calculated according to formula (1): The Scherrer formula is used to calculate the diffraction peak broadening caused by grain size, K is the shape factor (usually 0.9), λ is the X-ray wavelength, and the grain size d and dislocation density ρ of the copper alloy under different seawater flow rates are determined according to formula (2) and formula (3): With the increase of seawater flow rate, the axial tensile strain and dislocation density of copper alloy increase, indicating that high seawater flow rate will cause changes in the surface structural defects of the alloy, accelerate the corrosion process of copper alloy, and reduce its corrosion resistance. (2) Quantitatively simulate the mechanical effect of different seawater flow rates on the alloy surface. Based on the axial tensile microstrain ε determined in step (1), a microstructure model of the copper alloy with different seawater flow rates is established by atomic-level axial tensile strain: by regulating the lattice axial parameters, strain is applied along the (111) crystal plane direction. By precisely controlling the lattice constant of the copper alloy in the seawater environment, the lattice parameters in the (111) direction are gradually increased, and the axial tensile strain corresponding to the increase in flow rate is introduced. The lattice parameters in other directions are kept unchanged, thereby achieving atomic-level strain control applied to the (111) crystal plane. (3) Calculation of the dissolution potential of the copper alloy or the shift of the dissolution potential of the copper alloy under different seawater flow rates in a dynamic seawater environment: Based on the axial tensile microstrain determined in step (1) and the microstructure model under different seawater flow rates established in step (2), the energy of the alloy vacancy model under the action of different flowing seawater is calculated, and then the dissolution potential of the copper alloy or the shift of the dissolution potential of the copper alloy under different seawater flow rates is obtained; The energy E of the alloy model without axial tensile strain is determined by alloy and the energy of the alloy model under axial tensile strain and the energy E of the alloy vacancy model without axial tensile strain alloy-vac and the energy of the alloy vacancy model under axial tensile strain According to formula (4), the shift of the metal dissolution electrode potential caused by the introduction of tensile strain in copper alloy is calculated: By describing the dissolution electrode potential of metals during corrosion, the dissolution tendency of copper alloys in flowing seawater environments is quantitatively analyzed. As the seawater flow rate increases, the dissolution electrode potential of copper alloys shifts to the negative direction, resulting in a decrease in the metal dissolution potential and a decrease in corrosion resistance. This method is suitable for simulating the corrosion behavior of copper alloys in a dynamic seawater environment. (4) Calculation of the surface energy and work function of the copper alloy under different seawater flow rates in a dynamic seawater environment: Based on steps (1)-(3), by constructing a (111) crystal plane alloy structure model under different axial tensile strains, energy minimization calculations are performed to obtain the energy state of the alloy surface. By calculating the electric potential of the alloy model under different seawater flow rates and the contact potential difference between the alloy model and the seawater interface, the effect of seawater flow rate on the surface structure and stability of the copper alloy, i.e., the corresponding work function, is quantitatively analyzed. By determining the total energy E of the surface model with different axial tensions in step (2) slab and alloy bulk atomic N atoms The average energy E bulk According to formula (5), the surface energy state E of the alloy under different seawater flow rates is calculated. surf : The contact potential difference between copper alloy and seawater solution and the potential value ψ of the alloy model at different seawater flow rates, and the work function Φ required for the copper alloy to remove surface electrons at different seawater flow rates is calculated according to formula (6): As the seawater flow rate increases, the surface energy of the copper alloy increases, the work function decreases, the energy state of the atoms on the alloy surface increases, and electrons are more likely to escape from the surface, indicating that flowing seawater accelerates the corrosion kinetics of the alloy. (5) Calculation of activation energy barriers and dissolution rates of copper alloys under different seawater flow rates in a dynamic seawater environment: Based on steps (1)-(4), the activation energy barriers of copper alloy atoms under different flow rates are quantitatively analyzed using the transition state search method, and then the dissolution rate is calculated; The activation energy barrier ΔE(t) of alloy dissolution under different seawater flow rates was obtained by transition state search, where σ is the degeneracy of the reaction path and takes the value of 1, P 0 is the standard gas pressure of 0.1 MPa, t is the corresponding room temperature or atmospheric temperature, and h is Planck's constant of 6.626×10 -34 J.s,k b The Boltzmann constant is 1.381×10 -23 J.K. -1 , R is the universal gas constant 8.314 J·K -1 ·mol -1 , Δn=0 in the single molecule reaction, and the dissolution rate k under different seawater flow rates is calculated according to formula (7): TST : As the seawater flow rate increases, the dissolution activation energy barrier decreases significantly, the dissolution resistance of metal atoms decreases, and the dissolution rate increases accordingly. The effect of atomic-level axial tensile strain on the alloy corrosion kinetics under different seawater flow rates can be accurately evaluated, and the corrosion tendency of copper alloys in high flow rate environments can be simulated and predicted.

2. The method according to claim 1, characterized in that Copper alloy types include manganese aluminum bronze alloy (MAB) for propellers and copper nickel alloy (B10) for seawater pipelines; In step (1), the seawater flow rate of the manganese aluminum bronze alloy MAB used for the propeller is 0-12 m / s; In step (1), the seawater flow rate of the copper-nickel alloy B10 used for the seawater pipeline is 0-4 m / s.

3. The method according to claim 1, characterized in that In step (2), a copper alloy microstructure model is established based on atomic-level axial tensile strain. The method for simulating seawater flow rate is as follows: the axial tensile strain values ​​of the copper alloy at different seawater flow rates are obtained by XRD analysis, and the microstructure model of the copper alloy is established by using density functional theory (DFT). The lattice axial parameters are precisely controlled to apply strain, and the microstructure model of the copper alloy is established in the z direction of the (111) crystal plane. The vacuum layer releases the top two layers of atoms to simulate the alloy surface, while fixing the other layers of atoms to simulate the internal structure of the alloy, keeping the lattice parameters in other directions unchanged, gradually increasing the axial lattice parameters, introducing axial tensile strain corresponding to the increase in flow rate, and realizing atomic-level strain control of the copper alloy.

4. The method according to claim 1, characterized in that In steps (3)-(5), the simulation calculation method of the characteristic parameters of the corrosion kinetics of copper alloy under different seawater flow rates is as follows: the PBE generalized gradient approximation (GGA) method in the Materials Studio simulation package is used for geometric structure optimization, the Brillouin zone of the alloy surface is sampled on a (2×2×1) k-point grid by the Monkhorst-Pack method, the COSMO-type conductor shielding model is used, and the seawater dielectric constant is combined to simulate the seawater environment, an implicit seawater solvation model is established, and the DFT semi-core pseudopotential DSPP method is used to deal with the relativistic effect of nuclear electrons. The basis set adopts dual numerical plus polarization DNP, and the convergence tolerance and self-consistent field (SCF) convergence standard are set to 2.72×10 in the structural optimization. -3 eV to calculate the corrosion kinetic characteristic parameters of copper alloy in the dynamic environment of seawater.

5. The method according to claim 1, characterized in that In step (5), the calculation method of the dissolution rate and corrosion rate of the copper alloy under different seawater flow rates is as follows: using the transition state theory (TST) equivalent dissolution activation barrier, optimizing the dissolution transition state of the copper alloy in the seawater environment by the linear simultaneous transfer (LST) and quadratic simultaneous transfer (QST) methods, calculating the dissolution rate based on the Sobereva method, and establishing a linear relationship between the dissolution rate and the activation energy barrier.

6. A method for establishing a copper alloy corrosion rate prediction model based on atomic-level axial tension in a dynamic seawater environment, characterized in that: Based on the axial tensile strain model of copper alloy at different seawater flow rates in step (1)-step (2) of claim 1, the dissolution activation energy barrier is determined by transition state search, and a linear relationship between the dissolution rate and the activation energy barrier is established according to formula (7) to obtain the dissolution rate of copper alloy at different seawater flow rates. Combined with the intrinsic diffusion coefficient D of copper atoms, the correction coefficient k, the time conversion factor T and other parameters, several pairs of different seawater flow rate variables and the dissolution rate x are fitted, and the dissolution rate spectrum is converted into a relationship model x between the seawater flow rate and the copper alloy corrosion rate y under the dynamic seawater environment y=kDT 2 e C +α, the unit is mm / a (millimeter / year), where k is the correction coefficient, D is the intrinsic diffusion coefficient, T is the time conversion factor, α is the fitting coefficient, and C is a parameter related to the alloy, which can be obtained by fitting x and the dissolution rate to achieve accurate prediction of the corrosion rate of copper alloys in complex seawater environments.

7. The method according to claim 6, characterized in that The calculation method of the dissolution rate and corrosion rate of copper alloy under different seawater flow rates is as follows: the transition state theory (TST) is used to equate the dissolution activation energy barrier, the dissolution transition state of copper alloy in seawater environment is optimized by linear simultaneous transfer (LST) and quadratic simultaneous transfer (QST) methods, the dissolution rate is calculated based on Sobereva's method, and a linear relationship between the dissolution rate and the activation energy barrier is established. The intrinsic diffusion coefficient of copper atoms obtained by the Sutherland equation is used to convert the relationship between seawater flow rate and dissolution rate into a prediction model for corrosion rate in a dynamic seawater environment.

8. The method according to claim 6, characterized in that Corrosion rate prediction model of MAB alloy in seawater dynamic environment: R 2 =0.998, correction coefficient k1 = 1.91 × 10 -7 , the intrinsic diffusion coefficient of copper atoms D = 1.06 × 10 -7 , time conversion factor T = 3.15 × 10 7 , α = -20.34; Corrosion rate prediction model of B10 alloy in seawater dynamic environment: R 2 =0.996, correction coefficient k2 = 2.78 × 10 -9 , the intrinsic diffusion coefficient of copper atoms D = 1.06 × 10 -7 , time conversion factor T = 3.15 × 10 7 , β = -0.29.

Citation Information

Patent Citations

  • Pipeline corrosion rate prediction method and device and computer equipment

    CN110751339A

  • Metal atmospheric corrosion prediction method considering dynamic characteristics of natural environment

    CN113588528A

  • Method for detecting corrosion degree of metal material

    CN117451609A

  • Prediction method for corrosion resistance of magnesium

    CN117890288A

  • Corrosion / deposition rate calculation method and device of non-isothermal loop and electronic equipment

    CN118347924A